Transaction Costs of Low-Carbon Technologies and Policies : The Diverging Literature - Mundaca, Luis; Mansoz, Mathilde; Neij, Lena; Timilsina, Govinda R. (World Bank, Washington, DC, 2013)
Transaction costs are major challenge to moving forward toward low-carbon economic growth, as new technologies or policies tend to have higher transaction costs compared with those in the business as usual situation. However, neither a well-developed theoretical foundation nor a consensus interpretation is available for those transaction costs in the existing literature. The definitions and therefore the estimations of transaction costs vary across existing studies. The wide variations in the estimates could be attributed to several factors such as the very definitions and scope of transaction costs considered in the studies, the methodology for quantifying these costs, the type and size of low-carbon technologies, and complexities involved in the transactions. Nevertheless, the existing literature converges on addressing market failures, such as lack of information, in developing regulatory and institutional capacity to enhance private sector confidence in energy efficiency business as a key means to help reduce the transaction costs of low-carbon technologies.